1999
DOI: 10.1007/s000180050286
|View full text |Cite
|
Sign up to set email alerts
|

Calcium signaling in plants

Abstract: Changes in the cytosolic concentration of calcium ions ([Ca(2+)]i) play a key second messenger role in signal transduction. These changes are visualized by making use of either Ca(2+)-sensitive fluorescent dyes or the Ca(2+)-sensitive photoprotein, aequorin. Here we describe the advances made over the last 10 years or so, which have conclusively demonstrated a second messenger role for [Ca(2+)]i in a few model plant systems. Characteristic changes in [Ca(2+)]i have been seen to precede the responses of plant c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
40
0
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(46 citation statements)
references
References 113 publications
(181 reference statements)
4
40
0
1
Order By: Relevance
“…Pulses, repetitive oscillations, and sustained plateaus constitute elements of [Ca 2ϩ ] cyt signatures (Dolmetsch et al, 1997(Dolmetsch et al, , 1998Li et al, 1998), all of which have been detected in plant cells (Thuleau et al, 1998;Rudd and Franklin-Tong, 1999;Trewavas, 1999 (1) Replacement of W2 by alanine or deletion of terminal residues markedly reduced the ability of these Pep-13 derivatives to trigger the [Ca 2ϩ ] cyt response. These residues were previously reported to be essential for elicitor as well as competitor activity of Pep-13 (Nürnberger et al, 1994Zimmermann et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pulses, repetitive oscillations, and sustained plateaus constitute elements of [Ca 2ϩ ] cyt signatures (Dolmetsch et al, 1997(Dolmetsch et al, , 1998Li et al, 1998), all of which have been detected in plant cells (Thuleau et al, 1998;Rudd and Franklin-Tong, 1999;Trewavas, 1999 (1) Replacement of W2 by alanine or deletion of terminal residues markedly reduced the ability of these Pep-13 derivatives to trigger the [Ca 2ϩ ] cyt response. These residues were previously reported to be essential for elicitor as well as competitor activity of Pep-13 (Nürnberger et al, 1994Zimmermann et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Cytoplasmic free Ca 2 ϩ ([Ca 2 ϩ ] cyt ) serves as a second messenger in plant processes as diverse as root nodule formation, phytochrome phototransduction, stomatal closure, geotropism, circadian rhythm, pollen tube growth, and stress adaptation (Rudd and Franklin-Tong, 1999). Stimulusspecific and spatially and temporally defined Ca 2 ϩ signatures of characteristic magnitude, frequency, and duration are assumed to maintain signal specificity of transduction cascades (Thuleau et al, 1998;Trewavas, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Signaling to SI-Induced PCD Ca 2+ operates as a second messenger in many signaling cascades in both plant and animal systems, including PCD (Rudd and Franklin-Tong, 1999). [Ca 2+ ] cyt is known to play a pivotal signaling role in incompatible field poppy pollen; increased [Ca 2+ ] cyt is the earliest event triggered by SI Wu et al, 2011) that involves Ca 2+ influx (Wu et al, 2011 Franklin-Tong et al, 1997), Ca 2+ and K + influx (Wu et al, 2011), inhibition of sPPase activity (Rudd et al, 1996;de Graaf et al, 2006), depolymerization and stabilization of F-actin (Snowman et al, 2002;Thomas et al, 2006;Poulter et al, 2008Poulter et al, , 2011, and rapid inhibition of incompatible pollen tube growth.…”
Section: The Involvement Of the Vacuole In Cytosolic Acidification Anmentioning
confidence: 99%
“…Herein, signal information would be encoded by a specific Ca 2+ signature that is defined by precise control of spatial, temporal, and concentration parameters of alterations in cytosolic Ca 2+ concentration. The spectrum of stimuli that evoke such Ca 2+ elevations and their stimulus-specific characteristics has been cataloged and critically discussed in a number of informative reviews (Rudd and Franklin-Tong, 1999;Sanders et al, 1999;Knight and Knight, 2001;Sanders et al, 2002;Scrase-Field and Knight, 2003). Subsequent research suggested that while the shape and spatio-temporal distribution of Ca 2+ elevations could be of critical importance for stimulus response coupling , an additional level of regulation and specificity is achieved by Ca 2+ binding proteins that function as signal sensor proteins .…”
Section: Introductionmentioning
confidence: 99%